2014
DOI: 10.1111/jvim.12284
|View full text |Cite
|
Sign up to set email alerts
|

Selective Intestinal Cobalamin Malabsorption with Proteinuria (Imerslund‐Gräsbeck Syndrome) in Juvenile Beagles

Abstract: BackgroundSelective intestinal cobalamin malabsorption with mild proteinuria (Imerslund‐Gräsbeck syndrome; I‐GS), is an autosomal recessive disorder of dogs caused by mutations in AMN or CUBN that disrupt cubam function and which can present as a medical emergency.ObjectivesTo describe the clinical, metabolic, and genetic bases of I‐GS in Beagles.AnimalsFour cobalamin‐deficient and 43 clinically normal Beagles and 5 dogs of other breeds.MethodsClinical description and candidate gene genetic study. Urinary orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 23 publications
4
66
0
4
Order By: Relevance
“…Both cases presented with normocytic, normochromic, non-regenerative anaemia, compatible with previous reports in hypocobalaminaemic Beagles (Fordyce and others 2000, Fyfe and others 2014) and Border collies (Battersby and others 2005, Lutz and others 2013). Case 1 also had thrombocytopenia with hypersegmented neutrophils seen on examination of mesenteric lymph node aspirates.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Both cases presented with normocytic, normochromic, non-regenerative anaemia, compatible with previous reports in hypocobalaminaemic Beagles (Fordyce and others 2000, Fyfe and others 2014) and Border collies (Battersby and others 2005, Lutz and others 2013). Case 1 also had thrombocytopenia with hypersegmented neutrophils seen on examination of mesenteric lymph node aspirates.…”
Section: Discussionsupporting
confidence: 91%
“…To the authors' knowledge, this is the first report of this syndrome, confirmed by the commercially available genetic test, in Beagles from the UK that were successfully treated with parenteral cobalamin supplementation. The authors recognise that this disease has been seen in Beagles previously (Fordyce and others 2000, Barron and Wouda 2008, Fyfe and others 2014, Kook and others 2014, Kook and others 2015). …”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…It is an autosomal recessive trait caused by 2 distinct AMN mutations in Giant Schnauzers and Australian Shepherds . Our group and others recently identified 2 independent CUBN mutations in Border Collies and Beagles . Although the disease is rare, substantial carrier frequency has been noted in affected breeds and thus disease occurrence is more common regionally .…”
Section: Introductionmentioning
confidence: 89%